p53 Mediates Apoptotic Crisis in Primary Abelson Virus-Transformed Pre-B Cells - Unnikrishnan, Indira (American Society for Microbiology, 1999)
Transformation of pre-B cells by Abelson murine leukemia virus (Ab-MLV) involves a balance between positive, growth-stimulatory signals from the v-Abl oncoprotein and negative regulatory cues from cellular genes. This phenomenon is reflected by the clonal selection that occurs during Ab-MLV-mediated transformation in vivo and in vitro. About 50% of all Ab-MLV-transformed pre-B cells express mutant forms of p53 as they emerge from this process, suggesting that this protein may play an important role in the transformation process. Consistent with this idea, expression of p19(Arf), a protein whose function depends on the presence of a functional p53, is required for the apoptotic crisis that characterizes primary Ab-MLV transformants. To test the role of p53 in pre-B-cell transformation directly, we examined the response of Trp53(−/−) mice to Ab-MLV. The absence of p53 shortens the latency of Abelson disease induction but does not affect the frequency of cells susceptible to Ab-MLV-induced transformation. However, primary transformants derived from the null animals bypass the apoptotic crisis that characterizes the transition from primary transformant to fully malignant cell line. These effects do not require p21(Cip-1), a major downstream target of p53; however, consistent with a role of p19(Arf), transformants expressing mutant p53 and abundant p19 retain wild-type p19 sequences.